SAT0089 Empowering Patients to Use a Tablet Computer in Calculating Their Own Das Scores: Results of a Novel Study. (9th June 2015) - Karjigi, U.; Race, P.; Robinson, B.; Bridges, M.; Kumar, N.
Abstract : Background: The disease activity score (DAS 28) is widely used in clinical and research settings to monitor disease activity 1 . The DAS28 measure is also used by the National Institute for Health and Clinical Excellence (NIHCE) to monitor and treat RA 2 . The National Rheumatoid Arthritis Society (NRAS) is campaigning for all patients to "know their DAS" 3 . Patient reported DAS28 using paper based joint counts have shown to correlate with clinician assessed DAS28 4, 5, 6. If patients could be empowered to provide their own DAS measurements, this would not only encourage patient involvement, but save considerable amounts of clinician time. Using technology to make this easier may be better accepted by our patients. Objectives: Aim of the study is to compare the patient assessment of DAS28 using a Tablet Personal Computer (TPC) with clinician assessed DAS28. We also assessed patient's acceptability of using TPC using a Likert scale. Methods: A programme for calculation of the DAS score was developed for TPC in partnership with Grey Matters Healthcare. Each participant was taught how to score their DAS on the TPC. A clinician, blinded to the patient's self-score also calculated the DAS on the same TPC. Ethical approval and informed consent was obtained. Results: Mean age of participants was 60 years. Mean HAQ was 1.77. Mean DAS shown in Table 1 . The patient assessed scores were consistently higher than those calculated by healthcare staff. Using Wilcoxon matched pairs test there were significant differences in both ESR and CRP DAS scores between patients and clinicians, p<0.001. Spearman correlations were calculated and the score for DAS ESR was 0.84 and for DAS CRP was 0.75. There were no gender differences. The TPC had high acceptability with 67 (92%) patients stating that it was very easy or easy to use, only 1 individual said it was difficult due to painful joints Conclusions: Using the TPC is an acceptable method of self scoring DAS in patients with RA. In terms of absolute scores patients scored higher than clinicians. Therefore if an absolute score is required, e.g. in England for the prescription of biologic drugs, the use of patient scores would increase the use and therefore cost of RA treatment. The use of the TPC may however be an acceptable method of monitoring disease activity. References: Judging disease activity in clinical practice in rheumatoid arthritis: first step in the development of a disease activity score. D M van der Heijde, et al, Ann Rheum Dis. 1990 November; 49(11): 916–920. Rheumatoid arthritis: the management of rheumatoid arthritis in adults Clinical guidelines, CG79 - Issued: February 2009 www.nras.org.uk/DAS, February 2010 Patient self-administered joint tenderness counts in rheumatoid arthritis are reliable and responsive to changes in disease activity. Figueroa F et al, J Rheumatol. 2007 Jan;34(1):54-6 A patient-derived disease activity score can substitute for a physician-derived disease activity score in clinical research. Houssien DA et al, Rheumatology (Oxford). 1999 Jan;38(1):48-52. Validation of patient-reported joint counts in rheumatoid arthritis and the role of training. Levy G et al, J Rheumatol. 2007 Jun;34(6):1261-5. Epub 2007 Apr 15. Disclosure of Interest: None declared